The Akar Permasalahan dan Penanganan Kekerasan Seksual di Perguruan Tinggi - Putri Aisyiyah Rachma Dewi (Program Studi Ilmu Komunikasi Universitas Islam Majapahit, 2022)
On August 31, 2021 the Ministry of Research, Technology, Education and Culture (Kemristekdikbud) issued Ministerial Regulation No. 30 of 2022 which regulates the prevention and handling of sexual violence in higher education settings in Indonesia. This policy is a new hope for tertiary institutions, which are known as institutions with the highest rates of sexual violence compared to educational institutions at other levels (TK-SMA). In reality on the ground, one year after the Minister of Education and Culture was passed, there are many dynamics and obstacles faced by campuses in enforcing the rules. This paper is intended as a study that will be able to unravel the roots of sexual violence in tertiary institutions and how to deal with it, so that it can be a contribution of thought for one year's evaluation after Permendikbud No. 30 of 2021 is enacted. This research uses case study method. Data were obtained through in-depth interviews, documents, and field observations during September 2022. The results showed that Permendikbud No 30/2021 was not effective enough in resolving cases of sexual violence that occurred, due to several obstacles. In this study, it was found that there were at least 2 obstacles, namely the misogynistic culture which is still deeply rooted in the campus environment. Second, power relations and weak bargaining values.